Capacidad estatal para gestionar una ANP como la Reserva Nacional: El caso de la Reserva Nacional de Pampa Galeras Bárbara D’Achille en el Periodo 2018-2020 - García Huamaní, Rubén (2023)
This study focuses on understanding the state's capacity to manage the Pampa Galeras Bárbara D'Achille National Reserve (RNPGBA) in Peru during the period 2018-2020. Using a mixed-methods approach, the research also aims to determine the scope, achievements, and limitations of government policies imp lemented to safeguard the area and identify the key actors involved. A qualitative sample of seven key informants was taken. The results emphasize the relevance of the RNPGBA in vicuña protection and improving the well-being of the inhabitants. It was evident that, although regulations and plans have been enacted to manage the reserve, challenges persist regarding the active community participation levels and coordination among government entities. Key actors include state agencies, private entities, and the local communities, with a prominent role played by the Lucanas community. They have made progress in terms of species conservation and technical training; however, insufficient economic resources and inadequate government support hinder effective area protection. This study underscores the need for increased funding, specialized expertise, improved community organization, and enhanced connectivity to strengthen public environmental management in the reserve through coordinated collaboration among multiple stakeholders.